Proceso de atención de enfermería en paciente con pie diabético producido por diabetes mellitus tipo 2 - Joanna Cecilia, Proaño Erazo (2018)
Diabetic foot according to the WHO is defined as ulceration, infection and / or gangrene of the foot associated with diabetic neuropathy and different degrees of peripheral arterial disease, being the result of the interaction of different metabolic factors. The global prevalence of diabetes (DBT) is 5.1%; of which 20% will develop ulcers on the feet. More than 50% of non-traumatic amputations correspond to patients with diabetes. The chronology for the appearance of lesions is as follows: poor metabolic control; neuropathy and / or vasculopathy; external or internal trauma; pre-ulcerative lesion; ulcer; infection; necrosis and death. The triggers are: sensory-motor neuropathy; decrease in plantar pad; biomechanical alterations; traumatisms; peripheral vascular insufficiency. The present case called Process of nursing care in patient with diabetic foot produced by type 2 diabetes mellitus was performed in male patient of 50 years of age in the city of Babahoyo first semester of 2018. It was carried out in order to determine the process of nursing care in diabetic foot patients and analyze the patient's information through objective and subjective data that allow establishing the needs and health problems of the patient. The present case obtained favorable results for both the patient and the health personnel, being a patient collaborator and effectively concluding the chosen treatment, in order to have a maximum benefit and benefit of study, being for the scope and purpose in its preparation, hoping that it can serve as a parameter of indicator and source of information and thus reduce the various complications that this disease brings, and awareness that unhealthy habits could lead to death being a very high priority in public health.